STUDENTS' MOTIVATIONS FOR THE PHYSICAL EDUCATIONS PRACTICE AT THE 6TH AND 7TH GRADES OF FUNDAMENTAL EDUCATION (Fiep Bulletin - online, 2017)
Motivation is a set of biological and psychological mechanisms that makes possible the development of an action,orientation (for the objective or, instead, to move away of them) and ultimately, to the intensity and the persistence: the moremotivates is the person, more persistent and greater is the activity. (LIEURY & FENOUILLET 2000), during the people's dailyactivities, the motivational factors can suffer many oscillations, that is, there is a relative variety of the motivational factors by themotivation levels. Many factors are able to motivate the human being in their day-by-day routines, both internally as external(MACHADO, 1997). This paper tried to show which of the multiple factors presented in physical education in the schoolenvironment that motivates, or not, the students to participate the classes. It has been applied the questionnaire for students of the6th and 7th grades in a particular fundamental school in the city of Rio das Ostras – RJ. The principal results appointed were: thepleasure to practice physical activities was the principal factor that motivates students to participate the classes (23, 75%), thesecond reason was the pleasure to practice sports (21, 25%). The demotivating factors perceived in this searching were, the time ofthe class/ strong sun exposition (21, 14%), followed by the students' perceptions to being tired out easily (21, 43%). We observedthat the teachers were not appointed by the motivational factor (2, 5%) neither of demotivating factor (1,4%) for the physicaleducation practice. Therefore, the teacher and the school can work together to minimize the factors that creates disinterests of theclasses, scheduling the classes for milder temperatures using covered places to minimize de discomfort caused by sun. Lastly, asthe suggests, we understood that the most frequency of the practice of physical activity could promote the better students' motorcoordination and the increase of cardiorespiratory capacity, the largest goal of the physical educations as heath.